ANALISIS KEBERHASILAN IMPLEMENTASI SMILE DING DI KABUPATEN MADIUN (STUDI PADA DESA BLIMBING KECAMATAN DOLOPO) - Sari, Uthy Kemala; Ashar, Khusnul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
In essence, Indonesia's development is an effort to realize the rights of the Indonesian people, and is carried out according to the plan through national, provincial, district, and especially village plans. To realize an independent, prosperous, and developing village, several problems are still found in the village development planning process. One of the regencies in East Java, namely Madiun Regency, has made a new innovation called Smile Ding to be able to overcome these problems. This study aims to find out how the implementation of Smile Ding in Blimbing Village, to find out how the condition of Blimbing Village before and after the implementation of Smile Ding, and to find out the supporting factors and obstacles to the implementation of Smile Ding in Blimbing Village. This study uses a descriptive qualitative method based on field studies. Data collection techniques used are interviews with 6 informants and documentation. The results of this study indicate that village development planning with Smile Ding's innovation is appropriate and in line with applicable laws. The supporting factors for the implementation of Smile Ding in Blimbing Village include aspects of communication, resources, and the attitude of the implementers. While the inhibiting factor for the implementation of Smile Ding in Blimbing Village is the lack of quantity of human resources from village officials which will affect the distribution of potential.